Kinerja Peiayanan Jaringan Transportasi Jalan Nasional Trans Maluku Pulau Ambon - Sihaloho, Anotnius; Jinca, M Yamin (Warta Penelitian Perhubungan, 2012)
Trans Maluku is a national transportation network that links 12 island groups in Maluku Province. Island Group XII is Ambon Island that became PKN of Maluku province. This study aimed to find out ltaw tlte performance of the national road network in Island Group XII of Ambon Island and formulate development strategies. Analysis using quantitative descriptive method and SWOT analysis. 71ze results of the national road network Passo-Galala, Lahthalat- Batu Gantong and Waihaong-Batu Merah indicates that: indicators of accessibility, capacity and integrated quite effectively. Indicators are classified as not effective is Road Safety. The use of tire road network of relatively efficient aspects of tire VCR. Construction of support facilities necessary for the security of road users and an increase in financing the road network.